Hubungan intensitas kebisingan terhadap stres kerja pada pekerja di PT. X dan Y Palu - Sampe, Greyson Efraldi; Nayoan, Christin Rony (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
High-intensity noise in the workplace is the cause of work stress which has an impact on decreasing work productivity, work activities, and company income. This study intends to determine the relationship between noise intensity and work stress. This study applied the analytic observational type with the cross-sectional method. The determination of the sample was through a total sampling technique. The sample in this study was 30 workers at PT. X and Y. Sound level meter was used to measure noise intensity and The Depression Anxiety Stress Scale 21 was used to measure work stress. Spearman's test was used to analyze the data. The result of the Spearman test shows that the p-value is 0.484 (p > 0.05) and the correlation coefficient is -0.133 which indicates that there is no significant relationship between noise intensity and work stress therefore H₀ is accepted and H₁ is rejected. In conclusion, there is no relationship between noise intensity and work stress on workers at PT. X and Y.